Pengaruh Kepemimpinan, Motivasi Kerja Dan Tingkat Kesejahteraan Terhadap Karyawan PT Jasa Raharja (Persero) Cabang Bali - Harischandra, Ida Bagus Gamata; Utama, I Wayan Mudiartha (E-Jurnal Manajemen; Vol 3 No 2 (2014), 2014)
ABSTRACT PT Jasa Raharja is a company in the field of social insurance. Research conducted in PT Jasa Raharja (Persero) Branch Bali encountered problems that indicate poor performance. This study aims to answer the problem apakaha performance is affected by the leadership, motivation and welfare. Total population of 34 respondents. Methods of analysis using multiple linear analysis. The results showed simultaneous leadership, motivation, strong influence welfare. Partially, leadership, motivation, level probe welfare effect on employee performance Keywords: Leadership, performance, motivation, and welfare .
Keywords: Kepemimpinan, kinerja, motivasi, tingkat kesejahteraan